A meta-analysis comparing volar locking plates and cast immobilization for distal radius fractures in the elderly - Jingyi Yang; Yating Li; Xiaoyan Li; Nari Wulan (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Background The long-term outcomes (≥ 2 years of follow-up) of volar locked plate (VLP) fixation versus closed reduction and casting (CRC) for the treatment of displaced distal radial fractures (DRFs) remain unclear. This study aimed to conduct a meta-analysis comparing the long-term clinical outcomes of VLP and CRC in elderly patients (aged ≥ 60 years). Methods A comprehensive search of PubMed, Web of Science, and Cochrane Library was performed to identify studies comparing the long-term outcomes of VLP and CRC for DRFs. Only randomized controlled trials (RCTs) with a mean follow-up duration of at least 2 years and participants aged 60 years or older were included. The risk of bias in the included studies was assessed. The primary outcome measure was the Patient-Rated Wrist Evaluation (PRWE). Secondary outcomes included the Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire, EuroQol 5 Dimension 5-level score (EQ-5D-5 L), grip strength, and incidence of reoperation. Results Four RCTs, comprising 423 patients, were included. The meta-analysis revealed that VLP fixation was associated with significantly improved outcomes compared to CRC in terms of PRWE score (pooled mean difference: -6.21; 95% CI: -10.28 to -2.15; p = 0.003), DASH score (pooled mean difference: -8.18; 95% CI: -13.35 to -3.01; p = 0.002), and grip strength (pooled mean difference: -6.63; 95% CI: 0.25 to 13.01; p = 0.04). There were no significant differences in EQ-5D-5 L score (95% CI: -0.08 to 0.05; p = 0.74) or incidence of reoperation (RR = 0.56; 95% CI: 0.22 to 1.42; p = 0.22). Conclusions A two-year follow-up of displaced DRFs in elderly patients showed no significant long-term clinical advantage of VLP fixation over CRC.